Effect of Forced Physical Activity on the Severity of Experimental Colitis in Normal Weight and Obese Mice. Involvement of Oxidative Stress and Proinflammatory Biomarkers - Bilski, Jan (Nutrients, 2019)
Inflammatory bowel diseases are a heterogeneous group of disorders represented by two major phenotypic forms, Crohn’s disease and ulcerative colitis. Cross talk between adipokines and myokines, as well as changes in intestinal microcirculation, was proposed in pathogenesis of these disorders. C57BL/6 male mice were fed ad libitum for 12 weeks a standard (SD) or high-fat diet (HFD). After the adaptation period, two groups of animals fed SD or HFD were subjected to 6 weeks of the forced treadmill exercise and the experimental colitis was induced in both groups of sedentary and exercising mice fed SD and HFD by intra-colonic administration of 2,4,6-trinitrobenzenesulfonic acid. The disease activity index (DAI), colonic blood flow (CBF), the weight of animals, caloric intake, the mesenteric fad pad, the colonic oxidative stress markers malondialdehyde (MDA), reduced glutathione (GSH), and superoxide dismutase (SOD) activity and intestinal expression and protein content of proinflammatory markers were evaluated. Macroscopic and microscopic colitis in sedentary SD mice was accompanied by a significant fall in CBF and exacerbated in those fed a HFD. The contents of MDA, GSH, and SOD activity were significantly increased in both SD and HFD fed mice with treadmill exercise as compared with sedentary mice. In sedentary HFD mice a significant increase in the intestinal oxidative stress parameters and mucosal expression of IL-1β, TNF-α, IL-17, IFNγ, IL-6, and IL-10 protein were observed and these effects were aggravated in mice subjected to forced treadmill exercise. The mucosal expression of mRNA for TNF-α, IL-1β, iNOS, COX-2, SOD-1, SOD-2, GPx mRNAs, and the hypoxia inducible factor (HIF)-1α protein expression were upregulated in colonic mucosa of treadmill exercising HFD mice with colitis compared with those without exercise. We conclude that forced treadmill running exacerbates the severity of colonic damage in obese mice due to a fall in colonic microcirculation, an increase in oxidative stress, and the rise in expression and activity of proinflammatory biomarkers.